First language usage (l1) and learner retention on learning second language (l2) idiomatic phrases in tertiary level english as a second language (esl) classroom - Karunarathne, A.S. (University of Jaffna, 2022)
Purpose: This study was carried out to investigate the effect of first language (L1) usage and learner retention on learning second language (L2) idiomatic phrases in tertiary level English as a Second Language classroom (ESL). Twenty tertiary level ESL learners participated in this study. Methodology: Ten participants in the experimental group were taught the idiomatic expressions through L1 and ten participants in the control group were exposed to idiomatic phrases in the target language (L2) with individual sentences in order to learn the idiomatic expressions. Both groups underwent the same idiomatic expressions for a period of one month. At the end of the sessions, the same test has been given to the participants to check their understanding about idiomatic expressions taught. Findings: Results of the quantitative Findings indicated that the participants in the experimental group performed better than the participants in the control group. In order to get the perception of these two teaching methods, a questionnaire was distributed among the participants. The qualitative data gathered from the questionnaire indicated that the students in the experimental group could recall the English idioms for longer than the control group. Moreover the researcher was able to identify students' active involvement and enthusiasm in making creative sentences using English idiomatic phrases in L1, increased retention of idioms, low speaking anxiety, motivation to speak, learner autonomy in utilization of their own mnemonic situations, avoidance of cramming the facts and comprehensibility. Therefore, the study indicates that L1 has a positive effect on learning L2 idioms. Implications: The Findings could be used in order to encourage ESL teachers and learners to use L1 in teaching L2 idioms and might also attract the attention of learners to engage them in improving English speaking competency as it is an insightful teaching method.
Keywords: Idiomatic expressions; Target language; ESL classroom